A support architecture to MDA contribution for data mining. (31st March 2020) - Meskine, Fatima; Nait-Bahloul, Safia
The data mining process is the sequence of tasks applied to data, in order to discover relations between them to have knowledge. However, the data mining process lacks a formal specification that allows it to be modelled independently of platforms. Model driven architecture (MDA) is an approach for the development of software systems, based on the use of models to improve their productivity. Several research works have been elaborated to align the MDA approach with data mining on data warehouses, to specify the data mining process in a very high level of abstraction. In our work, we propose a support architecture that allows positioning these researches in different abstraction levels, on the basis of several criteria; with the aim to identify strengths for each level, in term of modelling; and to have a clear visibility on the MDA contribution for data mining.